A projective method for the construction of solutions of the problem of normal symmetric oscillations of viscous liquid - Barnyak, O. M. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We propose a variational formulation of the spectral problem of normal symmetric oscillations of viscous liquid. On the basis of this formulation, we construct a projective method for the determination of real eigenvalues of the problem. We present the numerical realization of this method in the case of a spherical cavity.